Editing the Translation of Ovid's Metamorphoses by Dr Joža Lovrenčič: New Evidence - David Movrin (Keria: Studia Latina et Graeca, 2018)
Editing the Slovenian translation of Ovid's Metamorphoses by Joža Lovrenčič (1890–1952), left as an unpublished manuscript, has led to the discovery of two original poetry collections by Lovrenčič, which had remained unpublished in the family archives after his death. The first collection, written in 1949, is titled No-one Nothing / in sad songs with a joyful accent / which he was singing about himself in third person / for fun and entertainment / when he went to Parnassus on foot. The other, Brother Honoratus: A Chronicle (1950), is a poetic rendering of a folk story heard by Lovrenčič in prison in August 1945, written in ten chapters. Both collections explore the position of inner exile.